BOC Signal Acquisition Algorithm Based on Similar Enfoldment. (25th February 2020) - Han, Qi; Zhu, Kejia; Hu, Caibo; Zhao, He; Wu, Shuang; Fu, Yu
Abstract : A BOC signal has been widely used in the Global Navigation Satellite System (GNSS). Although the BOC signal has many advantages, the autocorrelation function (ACF) of the BOC signal has lots of peaks, which makes signal acquisition difficult. This paper proposes a similar enfoldment acquisition (SEA) algorithm, which can be applied to sin-BOC and cos-BOC signals, with even and odd modulation orders. The SEA algorithm utilizes the similarity between the main peak and the secondary peak to construct a new ACF to eliminate the ambiguity of the BOC signal. This paper simulates the acquisition performance of the SEA algorithm, Martin algorithm, and SCPC algorithm, while the simulation result shows that the SEA algorithm is superior to the Martin algorithm and SCPC algorithm. Since the SEA algorithm does not need filters or auxiliary signals, its complexity is lower than that of the Martin algorithm and SCPC algorithm.